2020
DOI: 10.25251/skin.4.5.5
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Electrical Impedance Spectroscopy into Clinical Decisions for Pigmented Skin Lesions Improves Diagnostic Accuracy: A Multitiered Study

Abstract: Introduction: The number-needed-to-biopsy (NNB) metric measures the efficiency of a clinician’s ability to accurately diagnose and recommend pigmented skin lesions (PSLs) for biopsy for suspected melanomas. Electrical impedance spectroscopy (EIS) is a non-invasive technique that measures differences in resistance between healthy and cancerous skin cells, intended as an aid to enhance diagnostic accuracy.Methods: Dermatology clinicians of three distinct groups (residents, physician assistants/nurse practitioner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…EIS scores elevated the biopsy sensitivity of students close to that of dermatologists with images alone, suggesting particular value of EIS for novice diagnosticians. Moreover, this improvement in diagnostic accuracy among medical students is consistent with recent studies where the addition of EIS scores to clinical images alone increased diagnostic accuracy for novice diagnosticians, including trainees and midlevel practitioners [14][15][16] . Among the pigmented lesions specialists, the addition of an EIS score resulted in a trend toward improved accuracy of diagnosis, but it did not reach statistical significance.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…EIS scores elevated the biopsy sensitivity of students close to that of dermatologists with images alone, suggesting particular value of EIS for novice diagnosticians. Moreover, this improvement in diagnostic accuracy among medical students is consistent with recent studies where the addition of EIS scores to clinical images alone increased diagnostic accuracy for novice diagnosticians, including trainees and midlevel practitioners [14][15][16] . Among the pigmented lesions specialists, the addition of an EIS score resulted in a trend toward improved accuracy of diagnosis, but it did not reach statistical significance.…”
Section: Resultssupporting
confidence: 87%
“…The addition of EIS scores to clinical images resulted in more accurate biopsy decisionmaking by clinicians in survey studies. [14][15][16] . To date, however, the impact of EIS scores on clinician confidence in diagnosing lesions as benign or malignant remains unknown.…”
mentioning
confidence: 99%
“…While Rocha et al (60) concluded that EIS could avoid the need for follow-up in 46.9% of suspicious benign lesions included in the study, Ceder et al (59) affirmed that no additional malignant lesions were found with EIS at t = 3, during follow-up procedure. A study (65) detailing the performance of a multitiered system of decision support system reported that the inclusion of the EIS score in clinical decision making led to a reduction in the number of unneeded biopsies and that the amount of the reduction depends on a clinician's experience, i.e., 14.8% for resident, 16.8% for midlevel, and 16% for practicing dermatologist. More recently, a paraelectric spectroscopy technology has been used for skin cancer application in a correlational study (64).…”
Section: Skin Electrical Measurementsmentioning
confidence: 99%
“…Ceder et al (59) and Rocha et al (60) reported a specificity of 71% and 83%, respectively, employing the same technique in melanoma recognition. Recent studies (63,65) did not report TP, TN, FP, FN values and performance could not be analyzed. Ceder et al (59), with follow-up at 3 months, presented a sensitivity of 100% for a 70% specificity but the 95% CI were 3-100% and 48-89%, respectively.…”
Section: Studies Evaluationmentioning
confidence: 99%
“…EIS technology has been validated for pre-biopsy assessment of cancerous and high-risk pigmented skin lesions (PSLs) in a large prospective, multicenter, blinded study with over 2,000 patients [2]. EIS and dermoscopy have both been demonstrated to improve the selection of PSLs for biopsy [3,4,5]. The purpose of this study was to investigate whether EIS technology can further improve correct biopsy choices beyond clinical and dermoscopic evaluation for melanoma (MM), severe dysplastic nevi (SDN) and benign PSLs.…”
Section: Introductionmentioning
confidence: 99%